EFFECTS OF LINGUISTIC IMPERIALISM: A STUDY ON SEMANTIC NULLIFICATION AND PHONETIC AMBIGUITY - Ahmed, Iftikar Ali; Rajkhowa, Baishalee (International Journal of Research -GRANTHAALAYAH, 2025)
The expansion of language has been a part of human history since the dawn of time, and language imperialism is no exception. Assamese is the official language of the state of Assam, India and the mother tongue of the Assamese community. As we continue to delve into the nuances of language and its associated benefits, it is important to understand the implications of language imperialism and its ability to create catastrophic consequences, such as semantic nullification and phonetic ambiguity. Linguistic imperialism is a phenomenon where dominant languages are imposed on minority communities, leading to the loss of cultural identity and linguistic diversity. This paper will explore the negative impact of linguistic imperialism, specifically semantic nullification and phonetic ambiguity of the Assamese language. This paper will discuss how linguistic imperialism results in the loss of meaning in indigenous languages, the loss of unique sounds and pronunciation, and the impact on cultural identity.